PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR), UKURAN PERUSAHAAN, FINANCIAL LEVERAGE DAN MANAJEMEN LABA TERHADAP COST of EQUITY PERUSAHAAN - Bella Rinobel; Herry Laksito (Diponegoro Journal of Accounting, 2015)
This study aims to investigate the influence of Corporate Social Responsibility, Company Size, Financial Leverage, and Earnings Management to Cost of Equity companies. Corporate Social Responsibility is proxied by CSDI, firm size is proxied by total assets, financial Leverage is proxied by the Debt to Asset Ratio, and Earnings manajamen proxied by using the model Utami (2005), which measures the ratio of accrual based working capital to sales. while the dependent variables used in this study is the Cost of Equity companies proxied by using method (CAPM).             This study uses secondary data witch population of all companies listed on the Indonesia Stock Exchange (IDX) 2012-2013. The method used determine the sample of this study using purposive sampling. The analytical method used is multiple linear regression, and regression test before first tested the classical assumption.             Based on the results of the analysis carried out of the obtained results that Corporate Social Responsibility negative effect on the Cost of Equity company, Company Size positive effect on Cost of Equity company, Financial Leverage no effect on the Cost of Equity company and Earnings Management positive effect on Cost of Equity companies.